JBRMR 2017
DOI: 10.24052/jbrmr/v12is01/eopspjodapon
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perceived safety, procedural justice on domestic airline passengers of Nigeria

Abstract: KeywordsService recovery, procedural justice, perceived safety and Nigeria's domestic airline. AbstractThe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…This study also validates the findings of (Ringle et al, 2014;Haliru & Mokhtar, 2015), who found that perceived safety impacts consumers' satisfaction. Thus, hypothesis H1 is supported by data, and the findings of this study were able to address, conclude, and narrow the literature gap and validate a positive and statistically significant relationship between perceived safety and consumers' satisfaction with herbal medicine.…”
Section: Discussionsupporting
confidence: 89%
“…This study also validates the findings of (Ringle et al, 2014;Haliru & Mokhtar, 2015), who found that perceived safety impacts consumers' satisfaction. Thus, hypothesis H1 is supported by data, and the findings of this study were able to address, conclude, and narrow the literature gap and validate a positive and statistically significant relationship between perceived safety and consumers' satisfaction with herbal medicine.…”
Section: Discussionsupporting
confidence: 89%